2023
DOI: 10.3389/fphar.2022.1081978
|View full text |Cite
|
Sign up to set email alerts
|

The role played by ailanthone in inhibiting bone metastasis of breast cancer by regulating tumor-bone microenvironment through the RANKL-dependent pathway

Abstract: Introduction: Bone metastasis of breast cancer (BC) is a process in which the disruption of the bone homeostatic microenvironment leads to an increase in osteoclast differentiation. Ailanthus altissima shows an inhibitory effect on osteoclast differentiation. Ailanthone (AIL) refers to a natural compound isolated from Ailanthus altissima, a Chinese herbal medicine, and has effective anti-tumor activity in numerous cell lines. Its impact on bone metastases for BC is yet unclear.Methods: We measured the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Tribulus terrestris is commercialized with indications to improve sexual and athletic performance ( Stefanescu et al, 2020 ). It has been shown that extracts obtained from this plant exhibit inhibitory effects on CYP3A4 ( Wang et al, 2022 ). We have identified three reports of adverse events associated with the concomitant use of this adaptogen and the antidepressants metabolized by this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Tribulus terrestris is commercialized with indications to improve sexual and athletic performance ( Stefanescu et al, 2020 ). It has been shown that extracts obtained from this plant exhibit inhibitory effects on CYP3A4 ( Wang et al, 2022 ). We have identified three reports of adverse events associated with the concomitant use of this adaptogen and the antidepressants metabolized by this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…A similar test but on model lipid membranes has also been studied for medicinal and food applications [ 29 , 30 ]. The cytotoxicity of A. altissima against several tumor cells, such as HepG2 [ 31 , 32 ], HeLa [ 31 , 33 ], 786-O [ 31 ], A549 [ 31 , 34 , 35 ], Jurkat [ 36 ], R-HepG2 [ 37 ], MCF-7 [ 34 , 38 ], Hep3B [ 37 ], MDA-MB-231 [ 34 , 39 ], LAPC4, A375, B16 [ 40 ], and SGC-790 [ 41 ], has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several phytochemicals have been reported to display anticancer activity against cancer, including TNBC, such as resveratrol, indole-3-carbino, fisetin, 6-gingerol, curcumin, capsaicin, quercetin, ursolic acid, ailanthone, and cordycepin [25][26][27][28][29][30][31]. These phytochemicals reportedly target several molecular pathways implicated in carcinogenesis, including apoptosis, proliferation, inflammation, invasion, metastasis, angiogenesis, and chemoresistance [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Several phytochemicals have been reported to display anticancer activity against cancer, including TNBC, such as resveratrol, indole-3-carbino, fisetin, 6-gingerol, curcumin, capsaicin, quercetin, ursolic acid, ailanthone, and cordycepin [25][26][27][28][29][30][31]. These phytochemicals reportedly target several molecular pathways implicated in carcinogenesis, including apoptosis, proliferation, inflammation, invasion, metastasis, angiogenesis, and chemoresistance [25][26][27][28][29][30][31]. Multiple cellular signaling pathways implicated in tumor development and metastasis, such as TNF-α, Notch, Wnt-β, TGF-β, Ras, EGFR, INF-γ, hedgehog, TLR/NF-kB/NLR, PLK, CCNB1, PI3K/AKT, IL-1β, RANKL, SLUG, TWIST1, SNAIL1, and ZEB1, have been modulated by phytochemicals [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation